Developing a PJBL Module Based on Local Wisdom for Drama Writing - Rini Antika; Eko Firman Susilo; Saprida (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to develop and evaluate the effectiveness of a local wisdom-based module using the Project Based Learning (PJBL) approach to improve the drama text writing skills of grade XI students at SMA Negeri 1 Panai Hilir. Using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the module was validated by material, language, and media experts to assess its content, language quality, and visual design. The module was implemented in an experimental group and compared with a control group using conventional methods. Validation results showed a high feasibility score of 89.5%, categorized as "very feasible." The effectiveness test revealed that the experimental group improved by 21.5 points, while the control group improved by only 10.5 points. A t-test confirmed a significant difference (p < 0.05), and the N-Gain Score of 0.72 placed the module in the "high effectiveness" category. Observations and interviews further indicated increased student enthusiasm, creativity, and participation. These findings suggest that the PJBL-based local wisdom module is a practical, engaging, and culturally relevant tool for enhancing drama writing skills in high school students.